Leaders at war how presidents shape military interventions - Saunders, Elizabeth N. (Elizabeth Nathan) 1978- (Cornell University Press, 2011)
One of the most contentious issues in contemporary foreign policy-especially in the United States-is the use of military force to intervene in the domestic affairs of other states. Some military interventions explicitly try to transform the domestic institutions of the states they target; others do not, instead attempting only to reverse foreign policies or resolve disputes without trying to reshape the internal landscape of the target state. In Leaders at War, Elizabeth N. Saunders provides a framework for understanding when and why great powers seek to transform foreign institutions and societies through military interventions. She highlights a crucial but often-overlooked factor in international relations: the role of individual leaders.